PROSPECTS FOR THE DEVELOPMENT OF INNOVATION IN UZBEKISTAN AGRICULTURE (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
With an increase in the population, the demand for agricultural products is increasing. The introduction of innovative technologies in the sustainable development of this sector and the increase in the volume of agricultural products with the rational use of resources is gaining importance. In this article, an analysis of the current state of development of the agricultural sector of Uzbekistan, indicators of prospects and the main directions of innovative development were developed.